Longitudinal MRI and neuropsychological assessment of patients with clinically isolated syndrome - Uher, Tomas; Blahova-Dusankova, Jana; Horakova, Dana; Bergsland, Niels; Tyblova, Michaela; Benedict, Ralph H B; Kalincik, Tomas; Ramasamy, Deepa P; Seidl, Zdenek; Hagermeier, Jesper; Vaneckova, Manuela; Krasensky, Jan; et al. (Journal of neurology, 2014)
Cognitive impairment (CI) may occur in clinically isolated syndrome (CIS) patients. While the relationship between CI and magnetic resonance imaging (MRI) has been investigated extensively in multiple sclerosis (MS), MRI correlates of CI in CIS patients are unknown. To investigate the evolution of CI and to determine brain MRI structural correlates associated with CI in CIS patients. This prospective 24-month observational study examined 81 CIS patients treated with 30 µg of intramuscular interferon beta 1a once a week. MRI acquisition and neuropsychological (NP) assessment were performed at baseline, 6, 12 and 24 months. Participants were tested with Czech-validated version of Minimal Assessment of Cognitive Function in MS battery and MRI measures of lesion activity and burden, and global, tissue-specific and regional brain atrophy were performed. Over 24 months, 36 CIS patients developed clinically definite MS (CDMS). CI was observed in 10 (12.3 %) CIS patients at baseline and at the 24 months follow-up. Eight CIS patients changed their CI status over the follow-up (four improved and four worsened). No significant difference in development of CI was detected between stable CIS patients and those who developed CDMS. In multivariate regression and mixed-effect model analyses, no significant relationship was found between NP and MRI parameters. The lack of significant relationship between MRI metrics and cognition in this group of CIS patients could be attributed to several factors including the cognitive reserve, effect of disease-modifying therapy and relatively short follow-up period.
Keywords: Young Adult; Male; Middle Aged; progrese nemoci; magnetická rezonanční tomografie; mladý dospělý; Multiple Sclerosis; následné studie; Adolescent; Brain; Interferon-beta; kognitivní dysfunkce; Demyelinating Diseases; Adult; Prospective Studies; dospělí; mužské pohlaví; Disease Progression; Cognitive Dysfunction; mladiství; Follow-Up Studies; Neuropsychological Tests; kognice; lidé; interferon beta; ženské pohlaví; interferon beta 1a; Humans; mozek; Interferon beta-1a; neuropsychologické testy; Magnetic Resonance Imaging; Female; lidé středního věku; demyelinizační nemoci; roztroušená skleróza; Cognition; prospektivní studie